Indicadores de inclusão na educação infantil e suas implicações na constituição do sujeito - Freitas, Clariane do Nascimento de (2015)
This work is part of the Post-Graduate Education in Special Education Research Field at the Federal University of Santa Maria (UFSM), Rio Grande do Sul. The research addresses the process of inclusion in kindergarten theoretically based perspective historical and cultural whose main representative is Vygotsky. The research investigated the implications of interactions between children with and without disabilities in the constitution of the latter as a subject. Aimed to score factors revealing an inclusive approach; it identified the concepts that children interviewed have pointed out on disability and indicators denoting inclusive attitudes of these children. The locus of the research was the Children's education unit Ipê Amarelo, located at UFSM and participants were children enrolled in the institution between 2008 and 2012. The research was characterized as qualitative quantitative; whose instruments for data collection were semi-structured interview and the application questionnaire on the inclusion of indicators (BOOTH; AINSCOW, 2011). After there were two different analyzes of data collected and interviews were investigated through content analysis (BARDIN, 2008) and questionnaire replies interpreted from statistical quantification process. On first analysis it was found to Ipê could be characterized as an institutional space that had inclusion indicators. From this analysis, we sought to the words of children attitudes to indicate a collaborative behavior and less prejudiced front of colleagues with disabilities. It was found that each child had a concept of disability being identified: illness, difference and difficulty. In addition, all children expressed their belief in the learning potential of children with disabilities. It was also found that children are indicative of inclusion attitudes. Two aspects should be noted: first, it was understood that hardly children internalize values and knowledge in the same way because each has its individuality and uniqueness. Secondly, there were the contradictions in the statements of children. Even demonstrating positive attitudes towards disabled classmate, some children also expressed discomfort with these people. It is understood that the contradictions presented by the children interviewed are also experienced by the vast majority of adults, because living with someone who has an appearance or behave differently is not yet part of our culture. The understanding that it is fundamental defended that children are placed at an earlier age in a context where there is inclusive values because, as of established interactions, possibly internalize these values and thus will constitute subjects with more targeted behaviors to inclusion. So from the search results, it was understood that the hypothesis of an "inclusive subject" becomes possible from the moment the inclusive values are part of the context in which young children are interacting, it is this age group that they are forming their personality.